Pengembangan Media Pembelajaran IPA Berbasis Adobe Flash Cs6 Pada Materi Sistem Tata Surya Untuk Peserta Didik SMP Negeri 3 Panyipatan - Ihsanul Mukhlas; Yudha Irhasyuarna; Rizky Febriyani Putri (CV. ITTC INDONESIA, 2023)
The development of Adobe Flash CS6 media on the topic of the solar system aims to describe the validity, practicality and effectiveness of learning media. This research uses the Research and Development (R&D) method with the ADDIE (Analyse, Design, Develop, Implement and Evaluate) development model. The percentage method of media expert and material expert validation sheets was used in collecting this data. Test questions and surveys from students are also used. Adobe Flash CS6 learning media is known to have a media expert validity score of 86.67% and a material expert validity score of 87.71%, in accordance with research findings regarding the effectiveness of interactive learning media. Testing of interactive learning materials shows that it is effective for both individual students at 98.52% and small groups at 95.53%. However, the completion result is assessed at 80.00%. These findings provide strong evidence that solar system content created in Adobe Flash CS6 for use in junior high school science learning is very valid, practical, and effective.